2009
DOI: 10.1093/rheumatology/kep377
|View full text |Cite
|
Sign up to set email alerts
|

Platelet hyper-reactivity in active inflammatory arthritis is unique to the adenosine diphosphate pathway: a novel finding and potential therapeutic target

Abstract: Patients with active IA demonstrate enhanced platelet reactivity, unique to the ADP pathway. This potential pro-thrombotic bias may contribute to their increased cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…In addition to the in vitro exploration of these anti-platelet drugs, 96-well plate aggregometry has been used to describe ex vivo reactivity of platelets from patients with various diseases. Of note, enhanced platelet reactivity, particularly in response to ADP, has been described in patients with active inflammatory arthritis (27), HIV (28) and metastatic cancer (29). …”
Section: -Well Plate Aggregationmentioning
confidence: 99%
“…In addition to the in vitro exploration of these anti-platelet drugs, 96-well plate aggregometry has been used to describe ex vivo reactivity of platelets from patients with various diseases. Of note, enhanced platelet reactivity, particularly in response to ADP, has been described in patients with active inflammatory arthritis (27), HIV (28) and metastatic cancer (29). …”
Section: -Well Plate Aggregationmentioning
confidence: 99%
“…This reactivity pathway was also suggested to be a target in the treatment of these diseases. 33 Moreover, significantly decreased levels of MPV were reported after anti-TNF-a therapy in patients with AS. 20 Recently, MPV that was investigated in inflammatory bowel disease, 18 chronic obstructive pulmonary disease, 15 RA and AS [19][20][21] and PLR which was evaluated in some cancers like gastric, 14 colon, 22 and non-small cell lung cancers 23 have become to be prominent markers to indicate inflammatory status and prognosis of several diseases, but there is no cut-off level reported before for PLR and MPV as well as NLR.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, antagonists for these receptors may be potential targets for pathophysiological diseases linked to inflammation and articular cartilage resorption. Patients with RA have increased risk of cardiovascular disorders, and it was shown that there was an enhanced response of platelets to ADP in patients with RA [394].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%